P179 Life-time and recent recreational drug use is more common among men who have sex with Men compared to others attending sexual health clinics. (23rd May 2012) - Dargan, P I; Hunter, L; White, J A; Benzie, A; Wood, D M
Abstract : Background: Data on the frequency of recreational drug use (RDU) are collected at a population level through representative national surveys (eg, British Crime Survey). Anecdotally it appears that RDU is more common in men who have sex with men (MSM), but there are few systematic data to prove this. The aim of this study was to investigate the pattern of RDU in patients attending a sexual health clinic and to determine whether drug use was greater among MSM. Methods: We administered a questionnaire to all patients attending the sexual health clinics at two inner-city London teaching hospitals over a 3-month period (July 2011–September 2011). The questionnaire was self-completed by patients while waiting to see a clinician. Data were collected on age, gender, gender of sexual partner(s) and previous/current RDU (type and frequency of drugs used). Results: 1328 questionnaires were completed (mean±SD age 30.5±8.5 years, 54.9% female); 254 (19.1%) were MSM. Life-time use of all drugs, except cannabis, was more common in MSM; last-month use of all drugs, except cannabis, cocaine powder and amphetamine, was more common in MSM (abstract P179 table 1 ). Conclusion: Sexual health clinics provide an ideal forum to identify individuals using recreational drugs and to implement behavioural interventions and education programmes to promote safer RDU, reduce drug-related harm and, in view of the association between RDU and high risk sexual behaviours, to decrease the risk of subsequent STIs. Our data show that both life-time and last-month use of most recreational drugs are more common in MSM and therefore interventions should be targeted to this population.